Injuries, practices and perceptions of Australian wheelchair sports participants. Issue 2 (April 2021) - Osmotherly, Peter G.; Thompson, Erin; Rivett, Darren A.; Haskins, Robin; Snodgrass, Suzanne J.
Abstract: Background: Data regarding injuries in community-based wheelchair sport athletes is limited and long-term management of injuries and their impact upon participation unexplored. Little data examines benefits and barriers to wheelchair sports participation across the community. Hypothesis: The prevalence and nature of injuries sustained by wheelchair sports participants and injury prevention and management strategies will be associated with level of sports participation. Study design: Cross-sectional survey. Methods: Members of Wheelchair Sports New South Wales (WSNSW) completed a questionnaire developed from interviews with sports participants. Items examined demographics, sports played, injuries sustained, prevention and management practices, benefits and barriers to participation. Injury types and their management were collected for the previous 12 months. Results: Seventy-one questionnaires were returned. Injuries were sustained by 59% of respondents, with 28% reporting injuries in the past twelve months. Injuries most frequently affected the shoulder (25%), were primarily muscle strains (32%), and commonly caused by contact (48%). Injury prevention strategies were reported by 75% of respondents most commonly involving warm-up and stretching activities. Participation benefits included improvements in fitness (85%), opportunities for friendship (83%), improvements in self-care abilities (83%) and setting/achieving goals (91%). Barriers included cost of sports wheelchairs (68%), availability of competitions/competitors (62%), and distance required for travel for training/competition (71%). Conclusion: Injuries in wheelchair sports participants and benefits and barriers to participation are multi-faceted. Injury types, their management and prevention strategies were identified. Perceived benefits were found in the domains of health, socialisation and skills. Strategies aimed at raising participation rates should focus on promoting the physical, social and skill-related benefits.